2021
DOI: 10.3171/2019.12.jns191987
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in language cortex and white matter tracts after resection of dominant inferior parietal lobule arteriovenous malformations: a combined fMRI and DTI study

Abstract: OBJECTIVEThe dominant inferior parietal lobe (IPL) contains cortical and subcortical structures that serve language processing. A high incidence of postoperative short-term aphasia and good potential for language reorganization have been observed. The authors’ goal was to study the plasticity of the language cortex and language-related fibers in patients with brain arteriovenous malformations (BAVMs) located in the IPL.METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Combining the above, results in this study should be interpreted with caution, and future studies investigating causal relations in the network dynamics are strongly suggested. For instance, resting-state fMRI could be combined with structural MRI to investigate the possible topographical changes in the functional network (Salvador et al, 2005;Achard et al, 2006), building a weighted network with multi-modality approaches such as fMRI and DTI (Jiao et al, 2020), or using combined volume-based and tract-based approaches (Husain et al, 2011) along with graphtheoretical analyses to investigate the causal relationship between duration/severity and brain network topology.…”
Section: Limitationmentioning
confidence: 99%
“…Combining the above, results in this study should be interpreted with caution, and future studies investigating causal relations in the network dynamics are strongly suggested. For instance, resting-state fMRI could be combined with structural MRI to investigate the possible topographical changes in the functional network (Salvador et al, 2005;Achard et al, 2006), building a weighted network with multi-modality approaches such as fMRI and DTI (Jiao et al, 2020), or using combined volume-based and tract-based approaches (Husain et al, 2011) along with graphtheoretical analyses to investigate the causal relationship between duration/severity and brain network topology.…”
Section: Limitationmentioning
confidence: 99%
“…9). These local (short-range) cortical connections (involving both Wernicke and Geschwind territories and the convexity of the occipital cortex) play a role in the integration of visual stimuli in the verbal semantic processing and could play a role in the local plasticity phenomena supporting language recovery after restricted damage at the temporo-parieto-occipital junction in the left hemisphere (Sarubbo et al 2012;Jiao et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that cortical areas can undergo brain plasticity phenomena, much more relevant than white matter tracts ( 6 , 49 ). Based on these considerations, it becomes clear that the possibility to know in advance the location of the main white matter tracts and their relationships with a brain tumor constitutes a fundamental help for neurosurgeons approaching a brain tumor resection ( 50 53 ). DTI allows to reconstruct and visualize the most important white matter tracts on anatomical MR images of patients, permitting to build a personalized and complete surgical planning.…”
Section: Discussionmentioning
confidence: 99%